Functional electrical stimulation system and profile for walking - Abdul Malik, Noreha (IIUM Press, 2011)
Functional Electrical Stimulation (FES) helps to restore muscle function for dropped foot correction in patients having neurological disorders such as cerebro-vascular accident or stroke, multiple sclerosis and spinal cord injury by stimulating the tibialis anterior muscle or common peroneal nerve. As the result of stimulation, the patients are able to lift their foot during the swing phase of their walking. The stimulator is triggered by the sensor namely the footswitch that detects foot contact and un-contact with the ground during walking